2020
DOI: 10.1111/jphp.13284
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV ameliorates radiation-induced senescence via antioxidative mechanism

Abstract: Objectives Ageing is a universal and gradual process of organ deterioration. Radiation induces oxidative stress in cells, which leads to genetic damage and affects cell growth, differentiation and senescence. Astragaloside (AS)-IV has antioxidative, anti-apoptotic and anti-inflammatory properties. Methods To study the protective mechanism of AS-IV on radiation-induced brain cell senescence, we constructed a radiation-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Many effective components of GQBZD have been proved to have antiradiation effect. Li et al demonstrated that Astragaloside IV showed radio protective effects on the hematopoietic system in mice [ 27 ], and Liu et al suggest that Astragaloside IV can antagonize radiation-induced brain cells senescence, and its mechanism may be related to p53-p21 and p16-RB signaling pathways of aging regulation [ 28 ]. Yue et al found that Paeoniflorin enhances its sensitivity to radiotherapy by regulating MLH1 and MSH1 protein to enhance the DNA damage and repair ability of melanoma cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many effective components of GQBZD have been proved to have antiradiation effect. Li et al demonstrated that Astragaloside IV showed radio protective effects on the hematopoietic system in mice [ 27 ], and Liu et al suggest that Astragaloside IV can antagonize radiation-induced brain cells senescence, and its mechanism may be related to p53-p21 and p16-RB signaling pathways of aging regulation [ 28 ]. Yue et al found that Paeoniflorin enhances its sensitivity to radiotherapy by regulating MLH1 and MSH1 protein to enhance the DNA damage and repair ability of melanoma cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Agstragaloside IV, a major active compound extracted from the root of Huangqi, has extensive pharmacological activities, including anti-inflammatory, antioxidative, antiviral and anti-cancer functions (Liu, Shang, et al. 2020 ; Ge and He 2020 ; Hu et al. 2021 ).…”
Section: Antiviral Mechanisms Of Traditional Chinese Medicinesmentioning
confidence: 99%
“…Ionizing radiation- (IR-) induced DNA damage, senescence-associated inflammatory factors, and ROS are also hallmarks of cardiomyocyte senescence [ 21 ]. Senescence and the DNA damage-associated >BRCA1 and p53/p21 signaling axis regulated by IR can cause cardiovascular injury, which eventually leads to RIHD [ 22 , 23 ]. Cardiac cellular senescence can also manifest as inflammation- or ROS-induced telomere shortening and senescence-associated secretory phenotypes (SASPs) [ 16 , 24 ].…”
Section: Introductionmentioning
confidence: 99%